A Theoretical Framework of Knowledge Management Systems on Quality Management Systems - Nizam Mohammad, Mohammad Fakhrul; Abdullah, Rusli; Ab. Jabar, Marzanah; Haizan Nor, Rozi Nor; Mohd Nur, Nurhayati (Society of Visual Informatics, 2024)
Developing knowledge management systems (KMS) significantly supports, manages, or enhances the organization's knowledge management (KM) processes and activities. However, studies have shown that very few discussions focus on formulating the theoretical framework to support the development of KMS. Therefore, this paper aims to fill the void and gap in developing a more effective and efficient KMS. This study proposes a theoretical framework for KMS in the context of quality management systems (QMS), formulated based on three domain areas: established theories, knowledge management (KM) framework or model, and past KMS. This research output derived seven components of KMS (strategy, actors, KM process, source of knowledge, information management, continuous improvement, and infrastructure). This study has also contributed to the body of knowledge in KM by enriching the formulation of a theoretical framework for KMS. Although this study is conceptual and has yet to include the framework's validity and reliability testing, it has addressed a gap that can be potentially fulfilled and refined with more intense discussion and empirical studies.